Involvement of the median preoptic nucleus in blood pressure control - Silveira, Ludmila de Lima; Silva, Elaine Fernanda da; Andrade, Aline Mourao de; Xavier, Carlos Henrique; Freiria-Oliveira, Andre Henrique; Colugnati, Diego Basile; Castro, Carlos Henrique de; Colombari, Eduardo [UNESP]; Pedrino, Gustavo Rodrigues (Elsevier B.V., 2014)
Studies have demonstrated that median preoptic nucleus (MnPO) neurons play a role in organizing the cardiovascular responses induced by changes in the circulating blood volume. The present study examined whether the MnPO controls cardiovascular function. Male Wistar normotensive (NT) rats and spontaneously hypertensive rats (SHRs; 250-300 g) were anesthetized with urethane (1.2 g kg(-1), i.v.) and instrumented for recordings of mean arterial blood pressure (MAP) and renal blood flow (RBF). The renal vascular conductance (RVC) was calculated as the RBF:MAP ratio and was expressed as a percentage of the baseline value. In the NT rats (n = 6), MnPO inhibition produced a MAP reduction (-8.1 +/- 1.1 mmHg, p<0.05). In the SHRs (n = 6), the MAP response to MnPO inhibition was significantly greater (-22.3 +/- 4 mmHg, p<0.05) than in the NT rats. Furthermore, the increase in the RVC was higher in the SHRs (10.9 +/- 3.3%, p<0.05). Histological analyses confirmed that the injection sites were confined to the MnPO. We conclude that the MnPO is involved in the tonic regulation of blood pressure in NT rats. Moreover, the greater cardiovascular response to MnPO inhibition observed in the SHRs strongly suggests that the MnPO may contribute to the pathophysiology of essential hypertension. (C) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Blood pressure; Median preoptic nucleus; Hypertension; SHR